2020
DOI: 10.1071/sr19296
|View full text |Cite
|
Sign up to set email alerts
|

Soil structure characteristics, functional properties and consistency limits response to corn cob biochar particle size and application rates in a 36-month pot experiment

Abstract: The particle size (PS) and application rate (RA) of biochar influence soil–biochar interaction with concomitant effects on soil chemical and physical properties. However, limited studies exist that quantify how biochar PS and RA, acting solely or together affect soil structure characteristics and functional properties. This study investigated the effect of PS and RA of corn cob biochar on soil water retention (SWR) and aeration indicators such as relative gas diffusivity, structural characteristics su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…The data pertaining to electrical conductivity of postharvest soil as influenced by biochar as a component of integrated nutrient management is given in Table 4 RDF + biochar 2 t ha giving highest value of 0.46 dS m . This was also observed to be at par over all other treatments corroborating the previous findings (Obour et al, 2020;Usman et al, 2016;Agegnehu et al, 2015;Cely et al, 2015).…”
supporting
confidence: 90%
“…The data pertaining to electrical conductivity of postharvest soil as influenced by biochar as a component of integrated nutrient management is given in Table 4 RDF + biochar 2 t ha giving highest value of 0.46 dS m . This was also observed to be at par over all other treatments corroborating the previous findings (Obour et al, 2020;Usman et al, 2016;Agegnehu et al, 2015;Cely et al, 2015).…”
supporting
confidence: 90%
“…Garg et al (2020) explored gas permeability (k g ) of biochar-amended sandy soil at different degrees of compaction. Obour et al (2020) investigated the k g of sandy clay loam amended by corn cob biochar with two different particle sizes. However, existing studies considered a limited range of matric potential (i.e., near saturation).…”
Section: Core Ideasmentioning
confidence: 99%
“…Obour et al. (2020) investigated the k g of sandy clay loam amended by corn cob biochar with two different particle sizes. However, existing studies considered a limited range of matric potential (i.e., near saturation).…”
Section: Introductionmentioning
confidence: 99%
“…In sandy soil, biochar, which will be most effective when it has high porosity and an irregular shape [29], can improve physical properties [22] and soil water-holding capacity by changing the distribution of soil pores [30,31]. However, controlling the biochar particle size and application rate, Obour et al [32] found no significant overall change in the pore structure and function of the sandy loam tropical soil after 36 months of amending corn cob biochar. Jeffery et al [33] used biochar pyrolysis at 400 • C and 600 • C and mixed it with different proportions and found that the water-holding capacity of sandy soil did not change significantly.…”
Section: Introductionmentioning
confidence: 99%